2012
DOI: 10.4068/cmj.2012.48.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of General Dentists and Senior Dental Students in Iran about Prevention of Infective Endocarditis

Abstract: Infective endocarditis (IE) is an infection of the endothelial surface of the heart and heart valves with serious, even fatal, complications and that often requires long-term and expensive treatment. Dental procedures may lead to IE in high-risk patients. The aim of this study was to evaluate and compare the knowledge of general dentists and dental students concerning the prevention of IE in Hamadan, Iran. In this cross-sectional study, the awareness of general dentists and dentistry students concerning the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…According to the obtained findings, the overall knowledge level had direct significant relationship with age. Increase in the knowledge level of dentists with aging has been shown in several studies [ 44 , 45 ]. It seems that this relationship is the result of gaining professional experience in older dentists.…”
Section: Discussionmentioning
confidence: 96%
“…According to the obtained findings, the overall knowledge level had direct significant relationship with age. Increase in the knowledge level of dentists with aging has been shown in several studies [ 44 , 45 ]. It seems that this relationship is the result of gaining professional experience in older dentists.…”
Section: Discussionmentioning
confidence: 96%
“…The knowledge of participants regarding antibiotic prophylaxis was approximately good (over 75% correct answers), regardless of the methodological approach. In the available literature, mixed results were found for students' knowledge regarding this issue [16,32]. However, the students, who took part in the seminars (group A), stated that the dentist must make the indication for antibiotic prophylaxis.…”
Section: Comparison With Available Literaturementioning
confidence: 99%
“…These findings are as per those of in Iran, who found significant differences among dentists' knowledge about antibiotics prophylaxis against infective endocarditis according to their age groups (p=0.007), work experience (p=0.001), and sources of information (p=0.005), but not according to their gender. 17 Moreover, in Nigeria, they reported differences in dentists' knowledge on infective endocarditis according to their age (p=0.035), educational level (p=0.023), but not according to their gender. 18…”
Section: Discussionmentioning
confidence: 96%
“…In Iran, it was reported that participants' sources of information about infective endocarditis were textbooks (70.9%), journal articles (13.5%), and conferences (15.6%). 17 In Nigeria, it was reported that participants' sources of information about infective endocarditis were lectures (54.5%), internet (34.6%), and textbooks (2.2%). 18 Amoxicillin was the most commonly prescribed antibiotics by dentists in our study for prophylaxis against infective endocarditis (90.7%), followed by Augmentin (37.4%), while the timing of administering prophylactic antibiotics was stated to be 30-60 minutes before the procedure by the majority of participant dentists (86.8%).…”
Section: Discussionmentioning
confidence: 99%